Using The Language Game ShundÅ«q Al-AsyyÄ (Item Box) to Improve Students' Arabic Speaking Skills - Ardiansyah, Ade Arip; Kaffah, Tasya Silmy; Mukarom, Mukarom (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
Learning Arabic speaking skills still leaves problems in its implementation; problems with learning methods, media used, and a lousy learning environment are the root of the problem in this case. The same is true in class VIII MTs Al-Raudhah. Because there is no specific and continuous learning about Arabic speaking skills because mastering the skill of speaking Arabic cannot be obtained only by giving theory, but it takes practice and practice continuously. This study aimed to determine the improvement of Arabic speaking skills by applying the ShundÅ«q Al-AsyyÄ (item box) language game. The method used in this study is Classroom Action Research (PTK), carried out at MTs Al-Raudhah Cileunyi. The subject of this study was grade VIII MTs Al-Raudhah students for the 2022/2023 academic year. The number of students studied was 28 students, 18 female students and 10 men. Data collection techniques in this study are Observation, Questionnaire, Interview, Test, and Documentation. The results of the study stated that in the first cycle, before applying the ShundÅ«q Al-AsyyÄ (item box) game media, more precisely on the pretest results, the average speaking skill score achieved by students reached 60.04. After the first cycle, students' average speaking skills score increased to 77.32, although not perfect. (2) In the second cycle, precisely on the pretest, the results showed that the average score of students' speaking skills decreased to 70.46. After implementing the action, the average score of students increased to 87.43, and the average completion reached 89%. Therefore, using ShundÅ«q Al-AsyyÄ game media in class VIII MTs Ar-Raudhah Cileunyi can improve students' Arabic speaking skills. So, applying this media can be an alternative for teachers to improve students' Arabic speaking skills with fun. This research still has limitations and constraints, so it is expected that further researchers can develop and expand their research studies. <w:LsdException Lo